(untitled) - Bruner, Robert F. (Boston, 2007)
Case Studies in Finance links managerial decisions to capital markets and the expectations of investors. At the core of almost all of the cases is a valuation task that requires students to look to financial markets for guidance in resolving the case problem. The focus on value helps managers understand the impact of the firm on the world around it. These cases also invite students to apply modern information technology to the analysis of managerial decisions.
Keywords: Corporations,International business enterprises,Tập đoàn; Finance, Finance,Tài chính